Utilization of Red Mud-Fly Ash Reinforced with Cement in Road Construction Applications - Sarath Chandra K; Krishnaiah S; Kibebe Sahile (Advances in Materials Science and Engineering)
Industrialization is the key to the growth of any country’s economy. However, on the other hand, the production of industrial waste is increasing enormously, which adversely impacts the environment and natural resources. Red mud is also a widespread industrial waste produced during aluminium extraction from bauxite ore in Bayer’s process. Red mud is a highly alkaline material that creates a massive environmental threat in nature. To reduce the impact of this solid waste material, the ideal method is to use it in construction works with appropriate stabilization. This study envisages the strength properties of red mud with fly ash and cement to use it as a road construction material in the subgrade. The influence of fly ash and cement on improving the strength properties of red mud was studied in detail by replacing red mud with 10%, 20%, and 30% with fly ash and 1%, 3%, and 5% of cement to its dry weight. The CBR (California bearing ratio) value was increased from 1.58% to 11.6% by stabilizing red mud with fly ash and cement, which can be used as a road construction material. The UCS (unconfined compressive strength) of red mud was increased from 825 kPa to 2340 kPa upon curing for 28 days with the right mix of fly ash and cement. Along with the strength properties, the chemical analysis of leachate for the best suitable mix was performed according to the TCLP method to understand the hazardous materials present in the red mud when it is injected as ground material. Both strength properties and the leachate characteristics prove that the red mud with suitable fly ash and cement is an excellent material in road constructions.